Contemporary economic relations between China and European Union - Jokanović Nikola (Međunarodni Problemi, 2014)
This paper will discuss the economic relations between the European Union and the People’s Republic of China. The introductory part will make an insight into the position of China in the contemporary global economy. The following part of the paper will analyze China-EU trade relations. The topics included will be a general overview of these relations since their establishing in 1975 as well as the European Union’s attitude towards the Chinese WTO membership. The Sino-EU partnership and competition will also be described and it will be followed by an overview of the Sino-EU High Level Economic and Trade Dialogue (HED). The concluding topics in this part of the paper will include Sino-EU trade flows, perceived obstacles to trade and investment as well as recent trade disputes between two trading partners. The third part of the paper will deal with Sino-EU investment flows (with an emphasis on Chinese investments in EU member states). After the introductory remarks concerning the EU investments originating from China, the paper will shed light on particular EU member states which are preferred for Chinese investment as well as the industries in which Chinese companies are willing to invest. The concluding part of this paper will offer possible development of relations between the EU and China in the near future.